Self-identification in Mahua literature and Malay literature by Chinese Malaysian writers - Goh, Siew Poh (2013)
Since the late 60s, the Malay elites who rose up and expanded rapidly, has taken over the national administration. It was then followed by the promulgation of a number of policies e.g. New Economic Policy and National Culture Policy in the 70’s, which neglect the non-Malay rights. Under such circumstances, the rapport between the non-Malays and the state has always been the attention of researchers. In this study,the multiple relationships between Chinese Malaysian and the state are aimed to be explored by including Mahua literature, Malay literature by Chinese writers and Mahua literature in Malay translation into the scope of discussion. Specifically, this study investigates the identity and ethnic consciousness of Chinese Malaysian. Theoretical speaking, the subjectivity of Mahua literature can be recognized in the world of Malay literature through translation. However, the lack of cultural background knowledge by translators and concerned for the image of Mahua literature to other ethnic groups, caused to a situation where a large number of works worth sharing were not being translated. As for the Chinese writers of Malay literature, they did not manage to form a collective cultural identity because they were from diverse backgrounds. Lastly, the sense of cultural crisis was exhibited among the Chinese writers of Mahua literature when they were facing challenges from national policies. It exposed them to a risk of becoming “victim conscious” in which they will emphasize more the experience of being victimized in the country. In recent years, the democratization wave in Malaysia has brought a change to Mahua literature where the writers see themselves as a national citizen and thus shift their focus to local issues that are related to democracy.